Analysis of the Effect of Frequency Variation on SAR Test Results for Mobile Devices - Naila Widhyadari; Endah Setyowati (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
The rapid advancement of telecommunications technology led to an expansion of frequency spectrum usage, which raised significant concerns regarding human radiation safety. There was a lack of detailed data concerning how specific frequency fluctuations directly influenced the rate of electromagnetic energy absorption in human tissue. This study aims to provide a comprehensive analysis of Specific Absorption Rate (SAR) values across various frequency bands. A systematic evaluation was conducted to identify the correlation between frequency variation and energy absorption patterns. This research provides a critical contribution by establishing a clearer relationship between device operating frequencies and user safety compliance. The method involved a series of controlled tests across multiple frequency bands commonly utilized in cellular services. Electromagnetic simulations were performed to measure the energy distribution within body tissue models. The results indicated that frequency variation significantly influenced both the distribution and the peak absorption values. Higher frequencies tended to concentrate energy absorption within the surface layers of the body tissue rather than penetrating deeper structures. Furthermore, the data showed that as frequency increased, the absorption patterns became more localized. SAR values remained within international safety limits, yet showed distinct trends for each frequency interval tested. The findings confirmed that frequency was a primary determinant in electromagnetic interaction with biological systems. This study concluded that frequency variation must be a central consideration for establishing device compliance with safety standards. These results served as a foundational reference for optimizing transmission performance while maintaining safe radiation limits.